Musical and Bodily Predictors of Mental Effort in String Quartet Music: An Ecological Pupillometry Study of Performers and Listeners - Bishop, Laura; Jensenius, Alexander Refsum; Laeng, Bruno (Frontiers in Psychology, 2021)
Music performance can be cognitively and physically demanding. These demands vary across the course of a performance as the content of the music changes. More demanding passages require performers to focus their attention more intensity, or expend greater "mental effort'". To date, it remains unclear what effect different cognitive-motor demands have on performers' mental effort. It is likewise unclear how fluctuations in mental effort compare between performers and perceivers of the same music. We used pupillometry to examine the effects of different cognitive-motor demands on the mental effort used by performers and perceivers of classical string quartet music. We collected pupillometry, motion capture, and audio-video recordings of a string quartet as they performed a rehearsal and concert (for live audience) in our lab. We then collected pupillometry data from a remote sample of musically-trained listeners, who heard the audio recordings (without video) that we captured during the concert. We used a modelling approach to assess the effects of performers' bodily effort (head and arm motion; sound level; performers' ratings of technical difficulty), musical complexity (performers' ratings of harmonic complexity; a score-based measure of harmonic tension), and expressive difficulty (performers' ratings of expressive difficulty) on performers' and listeners' pupil diameters. Our results show stimulating effects of bodily effort and expressive difficulty on performers' pupil diameters, and stimulating effects of expressive difficulty on listeners' pupil diameter. We also observed negative effects of musical complexity on both performers and listeners, and negative effects of performers' bodily effort on listeners, which we suggest may reflect the complex relationships that these features share with other aspects of musical structure. Looking across the concert, we found that both of the quartet violinists (who exchanged places halfway through the concert) showed more dilated pupils during their turns as 1st violinist than when playing as 2nd violinist, suggesting that they experienced greater arousal when "leading'" the quartet in the 1st violin role. This study shows how eye tracking and motion capture technologies can be used in combination in an ecological setting to investigate cognitive processing in music performance.